Assessment of the implant geometry in fractionated interstitial HDR breast brachytherapy using an electromagnetic tracking system - Kellermeier, Markus; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (Brachytherapy, 2018)
PURPOSE: During the partial-breast treatment course by interstitial brachytherapy, electromagnetic tracking (EMT) was applied to measure the implant geometry. Implant-geometry variation, choice of reference data, and three registration methods were assessed. METHODS AND MATERIALS: The implant geometry was measured in 28 patients after catheter implantation (EMTbed), during CT imaging (EMTCT), and in each of up to n = 9 treatment fractions (EMTF(k), k = 1, 2,… n). EMTF(k) were registered to the planned implant reconstruction (CTplan) by using all dwell positions (DPs), the button centers, or three fiducial sensors on the patient's skin. Variation in implant geometry obtained from EMTF(k) was assessed for EMTbed, EMTCT, and CTplan. RESULTS: EMT was used to measure 3932 catheters. A duration of 6.5 ± 1.7 min was needed for each implant measurement (mean, 17 catheters) plus setup of the EMT system. Data registration based on the DP deviated significantly lower than registration on button centers or fiducial sensors. Within a registration group, there was a <0.5-mm difference in the choice of reference data. Using CTplan as reference for registration, the mean residual distance of DPs on EMT-derived DPs was found at 2.1 ± 1.6 mm (EMTbed), 1.3 ± 0.9 mm (EMTCT), and 2.5 ± 1.5 mm (EMTF(k)). CONCLUSIONS: EMT can assess the implant geometry in high-dose-rate interstitial brachytherapy breast treatments. EMTbed, EMTCT, and CTplan data can serve as reference for assessment of implant changes.
EVALuna2:36444